An Immune Mediated Pathology And Tissue Immune Responses Induced By Human Tuberculus Cryglobulin In A Murine Models - Alzamily, Khalid Yassen; Shnawa, Ibrahim M. S.; Al-Azzawi, Jalal A. (Journal of Kerbala for Agricultural Sciences, 2017)
Serum cryoglobulin were separated , characterized and partially purified from human pulmonary tuberculus patients. Three graded concentrations were made as;0.2,0.3,and 0.4 mg/ml .Four groups of mice, each of five were given 0.25ml. intramuscular in left and 0,25ml., in the right thigh to each animal in each group .the protocol consist of three successive doses from each concentration to each group in a week a part trend followed by one week leave .At the end of the protocol ,animals were sacrificed as well as the tissue blocks were collected, sectioned and processed for staining with H&E by the aim of tracing immune responses at tissue level .The immune response events were found as; Hyper-plasia of showed bronchus associated lymphoid tissue ,hyperplasia of epithelial cells of the bronchus walls, hyperplasia of macrophages in the alveolar spaces and accumulation of macrophages in the bronchial walls of the lungs .Cardiac muscles showed signs of carditis indicating type II hypersensitivity .Kidneys have shown inflammatory events indicating nephritis may be of serum sickness origin and edema can be of Arthus reaction, hypersensitivity type III. Liver sections were showing macrophage between blood vessels as pre-vascular kuff indicating delayed type hypersensitivity type IV. While splenic tissue sections were showing hypoplasia of lymphoid cells in the white pulp and /or deplition which may be attributed to the action of the regulatory T cells to the white pulp lymphoid cells. The tissue nature do affect the type of response as well as the intensity of the tissue responses were concentration dependent. Human cryoglobulin from tuberculus patients were found pathogenic for mice and the pathology was immune mediated as; Hypersensitivity types II,III, and IV as well as granuloma. The intensity of the responses were concentration dependent.